Comparison of Lower Limb Range of Motion in Male University Soccer Athletes with Ankle Injuries Versus Those Without - Qi Wang; Xiao Zhou; Mengxin Cui; Ziwen Mu; Hanyan Yan; Kazuhiro Imai; Shaoshuai Shen; Tomohiro Kimura; Hongtao Zeng (Applied Sciences)
In soccer players, ankle injuries are a common issue that may increase lower limb imbalance. Therefore, this study investigates the relationship between the range of motion of the knee and ankle joints and lower limb imbalance in soccer players with and without ankle injuries. We recruited 50 male university soccer athletes, who were categorized into an injury group (21 players) and a non-injury group (29 players). Prior to the experimental tests, basic data were collected through a self-reported questionnaire. During the experiment, participants sequentially completed a passive knee flexion test, a passive knee extension test, an active ankle plantarflexion test, and an active ankle dorsiflexion test. The results indicated that there were significant differences in the imbalance in knee and ankle range of motion between injured and non-injured athletes. Additionally, there was a significant negative correlation between right passive knee flexion range of motion, right active ankle plantarflexion range of motion, and ankle injuries.